Investment preferences and risk perception: financial agents versus clients - Kling, Luisa; König-Kersting, Christian; Trautmann, Stefan T. (Discussion paper series, 2019)
We study three fundamental components of financial agency settings: Perception and communication of investment profiles, the interaction of agents’ and clients’ preferences, and the role of (non-)monetary incentives. The perception of investment profile terminology is very heterogeneous, resulting in substantial miscommunication between clients and agents. Financial agents show a high willingness to implement their clients’ preferred investment profiles independent of monetary incentives. Agents’ investments for their clients are biased by their own investment preferences.
Keywords: Graue Literatur